The history of literature written facetiously - Romero, Leonardo (Tropelías: Review of Literary Theory and Comparative Literature, 2020)
This paper analyzes Manual de literatura para caníbales (2006 and 2016) by Rafael Reig, taking into account the humorous look that it projects on the history of Spanish literature through a saga of writers who act as witnesses of the literary life of the last two centuries.
Keywords: Rafael Reig; Manual de literatura para caníbales; history of literature; humor